Wind erosion in the Sahelian zone of Niger - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Wind erosion in the Sahelian zone of Niger by Geert Sterk 151pp ISSN 0926 9495